From Open‐Shell Singlet Diradicaloid to Closed‐Shell Global Antiaromatic Macrocycles - Li, Guangwu; Gopalakrishna, Tullimilli Y.; Phan, Hoa; Herng, Tun Seng; Ding, Jun; Wu, Jishan (Angewandte Chemie International Edition, 2018)
A dithieno[a,h]‐s‐indacene‐ (DTI‐) based diradicaloid DTI‐2Br was synthesized and its open‐shell singlet diradical character was validated by magnetic measurements. On the other hand, its macrocyclic trimer DTI‐MC3 and tetramer DTI‐MC4 turned out to be closed‐shell compounds with global antiaromaticity, which was supported by X‐ray crystallographic analysis and NMR spectroscopy, assisted by ACID and 2D‐ICSS calculations. Such change can be explained by a subtle balance between two types of antiferromagnetic spin–spin coupling along the π‐conjugated macrocycles. The dications of DTI‐MC3 and DTI‐MC4 turned out to be open‐shell singlet diradical dications, with a singlet–triplet energy gap of −2.90 and −2.60 kcal mol−1, respectively. At the same time, they are both global aromatic. Our studies show that intramolecular spin–spin interactions play important roles on electronic properties of π‐conjugated macrocycles. (Anti)aromatic macrocycles: Macrocyclization of open‐shell diradicaloids has led to closed‐shell global antiaromatic macrocycles, which could become global aromatic diradical dications upon two‐electron oxidation. The subtle balance of intramolecular spin–spin interactions plays the key role on the ground‐state electronic properties of these macrocycles.